Reduction of order formula and fundamental set of solutions for linear fractional differential equations. (August 2018) - Al-Refai, Mohammed
Abstract: In this paper, we consider a class of linear fractional differential equations involving the Caputo–Fabrizio fractional derivative of order 1 < α < 2 . We derive, in closed form, a reduction of order formula to obtain a second linearly independent solution. We then establish a fundamental set of solutions result to the equation. One example is presented to illustrate the validity of the obtained results.